Orientation Dependence of Dynamic Compared to Static Recovery in Interstitial Free Steel - Castro-Cerda, F (Acta Materialia Inc, 2024)
This study investigates the sub-structure of IF steel in three conditions: cold rolled, statically recovered, and warm rolled. After both cold and warm rolling, the steel exhibits the typical 〈110〉//RD and 〈111〉//ND fiber textures. Considering the short-range misorientation gradient ∆θ/∆x to assess locally stored energy variations, it was observed that 〈111〉//ND grains exhibit significantly higher gradients than 〈001〉//ND grains in all conditions. In the statically recovered conditions, the ∆θ/∆x values are significantly reduced compared to the cold rolled condition, but these values are significantly higher than those of the dynamically recovered after warm rolling. The strongly reduced orientation gradients in the 〈111〉//ND grains after warm rolling may reduce the nucleation potency of these orientations in the ensuing recrystallization. This study enhances our knowledge of deformation microstructure as a function of rolling temperature and is relevant in explaining reported differences in annealing textures during static recrystallization after cold vs warm rolling. © 2024 Acta Materialia Inc.